Effect of an exercise programme on reducing fall risk in older adults - Chia, Timothy Zun Yi (2019)
Background: Falls are the leading cause of injuries and often lead to functional impairment, disability and death among older adults (age ≥ 65 years). Current literature suggests that appropriately designed exercise interventions can prevent falls in older adults. There is however, a lack of effective exercise interventions that are easily implemented and accessible to the general older adult population. Purpose: To evaluate the effectiveness of an easily implemented community-based exercise programme such as, HPB’s “7 Easy Exercise to an Active Lifestyle” in reducing fall risk in older adults. Method: 15 older adults (13 women and 2 men, 72 ± 6 years) were recruited in a repeated measures study. Participants completed a 6-week multicomponent exercise programme adapted from Health Promotion Board (HPB)’s “7 Easy Exercise to an Active Lifestyle” programme that aimed to improve strength and balance. Fall risk was assessed pre and post-intervention using the Timed Up and Go Test (TUGT), with time taken to complete the test correlated with risk of falling. Wilcoxon Signed-rank test was used to compare time taken to complete the TUGT pre and post-intervention. Physical Activity Readiness Questionnaire for Everyone (PAR-Q+) was administered before each session to ensure the safety of participants and that they were physically able to participate. Results: Statistical analysis showed that time taken to complete TUGT post-intervention was significantly lower than pre-intervention (p=0.017). Conclusion: An easily implemented exercise programme such as, HPB’s “7 Easy Exercise to an Active Lifestyle” seems to be effective in reducing fall risk among community-dwelling older adults.